Efficacy and Safety of Camrelizumab in Combination with Docetaxel + S-1 Sequenced by Camrelizumab + S-1 for Stage III (PD-1+/MSI-H/EBV+/dMMR) Gastric Cancer: Study Protocol for a Single-Center, Prospective, Open-Label, Single-Arm Trial - Dong, Zhongyi; Ni, Bo; Yang, Linxi; Guan, Yujing; Zhu, Chunchao; Zhao, Enhao; Zhao, Gang; Xia, Xiang; Zhang, Zizhen (Frontiers in Surgery, 2022)
Background Gastric cancer occupies the fourth highest morbidity rate of cancers worldwide. A higher incidence of gastric cancer had been found in East Asia compared to the other regions. Gastrectomy with radical lymph node dissection is the cornerstone of curative treatment for Stage III gastric cancer, and postoperative systemic chemotherapy with docetaxel, S-1 improved patients’ disease-free survival rates. However, advances in immunotherapy bring innovations in the management of patients with gastric cancer. The objective of this study was to explore the efficacy and safety of camrelizumab in combination with docetaxel +S-1, sequenced by camrelizumab+S-1 in stage III gastric cancer patients who are EBV positive, with defective mismatch repair and CPS ≥5. Methods and analysis This prospective, open-label, single-arm trial was performed at Renji Hospital. In this study, a total of 70 adult patients aged 18–80 years with Stage III (PD-1+/MSI-H/EBV+/dMMR) gastric cancer confirmed by post-operative pathology will be enrolled after screening. Participants will receive the specific chemotherapy regimen until 1 year after the operation or until tumor recurrence or metastasis. The primary outcome is the 3-year disease-free survival rate measured by the Clopper-Pearson method and 95% confidence intervals. The secondary outcomes include overall survival, incidence and severity of adverse effects, and laboratory abnormalities. The data will be analyzed by the Kaplan-Meier method and log-rank test. The patients will be followed up every 3 months with imaging investigation until clinical remission. Ethics and dissemination All participants will provide informed consent. The protocol has been approved by the Shanghai Jiaotong University School of Medicine, Renji Hospital Ethics Committee (KY2019-191). The results will be disseminated through peer-reviewed manuscripts, reports and presentations.